Antifertility Effects Of Single Oral Doses Of Triptolide In Male House Rat (Rattus Rattus L.) (Applied Biological Research, 2014)
The aim of present study was to evaluate the effect of single oral doses of triptolide on fertility of male house rat, Rattus rattus. Single oral  administration of triptolide to male R. rattus resulted in 16.67 and 33.33%  mortality in rats treated with 100 and 150 mg kg-1b.wt. of triptolide,  respectively, within 1-3 days of treatment. The LD50 value of triptolide  against male R. rattus was found to be 182.81 mg kg-1 b.wt. Autopsy of rats  surviving till day 45 after treatment revealed no significant effect on  weights of reproductive organs. The sperm motility and viability in cauda  epididymal fluid were reduced significantly in all the treated groups.  Sperm concentration was significantly reduced only in rats treated with  100 mg kg-1 b.wt. of triptolide. Treatments significantly affected sperm  morphology. The sperms with head tail separation ranged from 15.8 to  24.0% in all treated groups. The present study suggests the potential of  triptolide in regulating fertility of male R. rattus.
Keywords: Antifertility; Rattus rattus; single dose; triptolide